Fe3O4@ZrO2/SO42‐: A recyclable magnetic heterogeneous nanocatalyst for synthesis of β‐amino carbonyl derivatives and synthesis of benzylamino coumarin derivatives through Mannich reaction. (24th November 2017) - Ghafuri, Hossein; Ghorbani, Behnaz; Rashidizadeh, Afsaneh; Talebi, Majid; Roshani, Mahdi
Abstract : In the present work, we developed an effective protocol for the synthesis of β‐amino carbonyl compounds and synthesis of benzylamino coumarin derivatives through Mannich type reaction in high yields. Fe3 O4 @ZrO2 /SO4 2‐ was employed as an effective heterogeneous nanocatalyst for the Mannich reaction. This research consists of two sections. In first section, β‐amino carbonyl derivatives were synthesized under solvent‐free condition. In the other section, benzylamino coumarin compounds were synthesized at room temperature. The present approach offers several advantages such as short reaction times, low cost, easy work‐up, mild reaction conditions, high yields and ease of recovery and reusability of the catalyst without significant loss of activity. Abstract : We developed an effective protocol for the synthesis of β‐amino carbonyl compounds and synthesis of benzylamino coumarin derivatives through Mannich type reaction in high yields. Fe3 O4 @ZrO2 /SO4 2‐ was employed as an effective heterogeneous nanocatalyst for the Mannich reaction. The present approach offers several advantages such as short reaction times, low cost, easy work‐up, mild reaction conditions, high yields and ease of recovery and reusability of the catalyst without significant loss of activity.